Rethinking the Justice of God with Asian Sensibilities - Clarence S Devadass (P3TK, Sanata Dharma University, 2019)
This article proposes the need to rethink the concepts of justice with Asian sensibilities. For centuries the idea of justice has been read and interpreted along and within the classical Greek philosophical framework. In some ways, this Greek categorial framework is also seen in the concepts of biblical justice. However, in an Asian context, the character justice and its application need to be explored in the light of restoring harmony, with the self, other, cosmos and God, which is integral in many of the Asian spiritualities. In modern times, the theories of John Rawls and Robert Nozick are much quoted in studies regarding justice. However, Asian sensibilities call for a deeper exploration of justice for the purpose of harmony and that is the intent of this article.